Hank The Cowdog: The Case of the Monkey Burglar #48 - Erickson, John R. 1943-; Holmes, Gerald L. (New York : Viking, 2006)
Hank learns about a tool thief on the loose who uses a monkey to help him do his dirty work.
008-up.
Keywords: Hank the Cowdog (Fictitious character) -- Fiction; Monkeys -- Fiction; Burglars -- Fiction; Dogs -- Fiction; Ranch life -- Fiction -- West (U.S.); Hank the Cowdog (Fictitious character) -- Fiction; Monkeys -- Fiction; Dogs -- Fiction; Ranch life -- Fiction -- West (U.S.); Humorous Stories; Mystery and detective stories; West (U.S.) -- Juvenile literature; West (U.S.) -- Fiction; Western stories; Fiction; Fiction